Spark plasma sintering of fine uranium carbide powder. Issue 1 (January 2017) - Salvato, D.; Vigier, J.-F.; Cologna, M.; Luzzi, L.; Somers, J.; Tyrpekl, V.
Abstract: Results of uranium carbide sintering using a spark plasma sintering facility are presented here. The initial uranium carbide powder is produced from the thermal decomposition of a citric acid and uranium nitrate mixture. The study shows that spark plasma sintering is a very efficient compaction tool for uranium carbide material. Both onset of sintering and final density are strongly correlated to the UC synthesis conditions. Graphical abstract: